Students’ Perceptions toward Teacher’s Teaching Strategies, Personal Competence, and School Facilities - Nurul Fajriah; Sofyan A. Gani; Iskandar Abdul Samad (English Education Journal, 2019)
This study was aimed to find out alumni’s perceptions toward English teachers’ teaching strategies and personal competences. In addition, this research investigated how students perceived availabilty of their school facility. The study was conducted online by sending the link of questionnaire to alumni who graduted from three state senior high schools in South Aceh. The study used the quantitative method with the survey design, and the questionnaire was used as the instrument to get the data needed. The population of this survey was all students who graduated from SMAN 1 Labuhanhaji, SMAN 1 Tapak Tuan, and SMAN 1 Trumon and they are now continuing their study at some universities and academies in Aceh and North Sumatera. The samples for this study were fifteen alumni chosen from each of these three state schools. The collected data was analyzed through a quantitative procedure by using a statistical formula to find the percentage of each statement. The results showed that most English teachers were perceived not to thoroughly apply the strategies suggested in English teaching but have a complete set of required personality to be a good teacher. In addition, school facilities were perceived still insufficient.